2022
DOI: 10.1002/gch2.202200046
|View full text |Cite
|
Sign up to set email alerts
|

Reclaimed and Up‐Cycled Cathodes for Lithium‐Ion Batteries

Abstract: As electric vehicles become more widely used, there is a higher demand for lithium‐ion batteries (LIBs) and hence a greater incentive to find better ways to recycle these at their end‐of‐life (EOL). This work focuses on the process of reclamation and re‐use of cathode material from LIBs. Black mass containing mixed LiMn 2 O 4 and Ni 0.8 Co 0.15 Al 0.05 O 2 from a Nissan Leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
(77 reference statements)
1
14
0
Order By: Relevance
“…However, since then ICP-OES analysis of dismantled first-generation Nissan Leaf cells from the same battery pack has revealed that the cathode chemistry is LMO and NCA. 39 The results from this experiment confirm that the content ratio of LMO to NCA in the blended cathode is approximately 3:1.…”
Section: Xrd Measurementssupporting
confidence: 64%
See 1 more Smart Citation
“…However, since then ICP-OES analysis of dismantled first-generation Nissan Leaf cells from the same battery pack has revealed that the cathode chemistry is LMO and NCA. 39 The results from this experiment confirm that the content ratio of LMO to NCA in the blended cathode is approximately 3:1.…”
Section: Xrd Measurementssupporting
confidence: 64%
“…Experiments were carried out on automotive large-format pouch cells (blended cathode consisting of lithium manganese oxide (LMO) with lithium nickel-cobalt-aluminium oxide (NCA), and graphite anode) extracted from two first-generation Nissan Leaf battery modules. 39 arrangement and to establish a connection with busbars, cell tabs were cut during manufacturing depending on the position in the module (Figure 1b). For analysis in this study, two middle cells (No.…”
Section: Battery Specificationmentioning
confidence: 99%
“…34 It is worth mentioning that the recycling process reported in this work shows not only a low energy cost of about 350 W per h per cell but also drastically lower CO 2 emission compared with the industrial production of Al and Cu foils. 20,22 Fig. 2a and c show survey-scan XPS spectra of Al and Cu current collectors.…”
Section: Surface Composition and Morphologymentioning
confidence: 99%
“…Complete removal of Al and Cu is therefore beneficial for improving subsequent recovery efficiency with fewer purification processes. 21,22 With these issues in mind, direct reuse of current collectors provides an even better option than conventional recycling, which can not only solve LIB waste problems but also skip various recycling processes, retaining the embedded environmental and economic benefits. Some publications have proposed the possibility of direct reuse of current collectors in the literature, 23,24 however, there is a lack of experimental work on the direct reuse of current collectors to date.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, in the recycling of waste lithium batteries, there is often more than one type of lithium battery, and the recycling process will be more complex, which is one of the reasons why more and more scholars have focused on the recycling of mixed LIBs in recent years. Gastol et al (2022) recycled and regenerated the black mass obtained by shredding and disassembling, respectively. The disassembly and comminution process for cathode black block recovery is shown in Figure 6C.…”
Section: Mixed Regeneration Of Spent Libsmentioning
confidence: 99%